How nostalgic taste on the screen stimulates the consumption of time-honoured restaurants: The mediation role of parasocial interaction - Yang, Jian; Tang, Jianle; Zhang, Lingmin (Frontiers in Psychology, 2022)
As a unique cultural asset, time-honoured restaurants carry the crystallisation of traditional cuisine and the spirit of artisanship with an inestimable value. Nostalgia is a characteristic element of time-honoured restaurants and the central theme of their online marketing. However, few studies have examined the effect of nostalgia evoked in bloggers' content on consumer behaviour in the context of time-honoured restaurants. To ﬁll this gap, this study used the SOR model as an underpinning theory and selected parasocial interaction among bloggers and viewers as mediation to examine how the nostalgic taste on the screen affected behavioural intention towards time-honoured restaurants. Emotional involvement and credibility were also added as variables to enrich the research framework from cognitive and affective perspectives. A PLS-SEM approach was used to analyse the research models, including evaluating the measurement and structure models. The result, tested by the online survey data from 319 valid responses, demonstrated that nostalgia evoked in bloggers' content can directly facilitate parasocial interaction or indirectly through credibility and emotional involvement, resulting in behavioural intention. The fully mediating role of parasocial interaction between emotional involvement and behavioural intention was also confirmed. The findings of this study offer theoretical and practical implications, highlighting the critical roles of nostalgia and parasocial interaction in the mechanism that online stimulus influences realistic behavioural intention, and therefore exploring a way forward for time-honoured restaurant marketing that fits in with the online media age.